EFFICIENCY OF INTRA-ARTICULAR INTRODUCTION OF BETAMETASON FOR PATIENTS SUFFERING FROM JUVENILE RHEUMATOID ARTHRITIS - E.I. Alexeeva; I.E. Shakhbazyan; E.Yu. Afonina; S.I. Valieva; T.M. Bzarova; E.G. Chistiakova ("Paediatrician" Publishers LLC, 2006)
The work studied efficacy of local intra-articular application of betametason for treating juvenile rheumatoid arthritis. The survey findings of 50 children locally treated with betametason have revealed that the medication has a distinct local anti inflammatory effect. The findings are based upon statistically reliable reduction of articular syndrome activity (number of painful and increasedasize joints, pain index and exudation) with all patients. Along with a local effect, betametason had a systematic antiainflammatory effect, which leads to reduced intensity or total disappearance of inflammation symptoms in non punctured joints as well, and to reliable reduction of ESR. Local application of betametason cut short nonasevere syndrome of glucocorticoids cessation with arthralgia, low grade fever, nausea, vomitus, muscular tremor, arterial hypotension, depression and asthenia. Local inta-articular introduction of betametason may be applied as a substitution therapy for patients with reduced or discontinued intake of peroral glucocorticoids, provided an active synovitis is present. Key words: juvenile rheumatoid arthritis, betametason, glucocorticoids, treatment, children.